Numerical modelling of accidental gas release in a gas turbine enclosure- Evaluation of notional nozzle models and dispersion modelling using RANS, URANS and LES methods - Forsell, Martin (My University, 2019)
In the event of an accidental gas leak in an industrial facility it is important that gas is not collected in a cloud of sufficiently large size and concentration that an explosion could occur. When evaluating the effect of an accidental gas release, the leak and the dispersion of potentially explosive gases must be modelled in a manner that is accurate and conservative. The work presented in this report can be divided into two main parts. The first part concerns the modelling of the leak itself and what shape of the leak hole is appropriate to use. Jets exiting from circular, rectangular and elliptic orifices of different aspect ratios have been evaluated. Ways to model the hypersonic nearfield of the leak using notional nozzle submodels have been compared to a simulation of an equivalent hypersonic jet. Methane is used for modelling the leaked gas as it is the main constituent of natural gas. The second part concerns ways to model the turbulent mixing of the leaked gas with ambient air. Two turbulence modelling approaches have been evaluated: URANS and LES. Steady RANS was found to not be a suitable approach for simulating the flow in the gas turbine enclosure even with no leak implemented. Results indicate that the circular shape is the preferable choice regarding leak hole shape.The notional nozzle model called the Adiabatic expansion approach appears to be both conservative and highly accurate. Simulations of the gas leak in a gas turbine enclosure using LES in combination with the Adiabatic expansion approach produces a considerably smaller explosive gas cloud volume compared to when URANS is used with the same notional nozzle model. This effect was not seen however when comparing URANS and LES when the Sonic jet approach was used as a notional nozzle. This could be due to the lower velocity of the jet produced with the Sonic jet approach which in turn might cause less turbulent mixing.
Keywords: URANS; LES; mixing; leak; notional nozzle; accidental gas release; fictional nozzle; submodel; methane jet